2020
DOI: 10.3390/jintelligence8010009
|View full text |Cite
|
Sign up to set email alerts
|

How Approaches to Animal Swarm Intelligence Can Improve the Study of Collective Intelligence in Human Teams

Abstract: Researchers of team behavior have long been interested in the essential components of effective teamwork. Much existing research focuses on examining correlations between team member traits, team processes, and team outcomes, such as collective intelligence or team performance. However, these approaches are insufficient for providing insight into the dynamic, causal mechanisms through which the components of teamwork interact with one another and impact the emergence of team outcomes. Advances in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Empirical substantiation of such claims has proven difficult, however. Most investigations rely heavily on laboratory-derived summaries or “snapshots” of individual and collective behavior that flatten the complexity of local scale interactions [ 20 ] and make it difficult to examine causal relationships between individual scale mechanisms and collective behavior as they typically unfold in real world settings [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical substantiation of such claims has proven difficult, however. Most investigations rely heavily on laboratory-derived summaries or “snapshots” of individual and collective behavior that flatten the complexity of local scale interactions [ 20 ] and make it difficult to examine causal relationships between individual scale mechanisms and collective behavior as they typically unfold in real world settings [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, swarm intelligence provides tools and a theory to understand the dynamics of opinion emergence, spreading, and competition in networks of highly correlated individuals (O’Bryan et al, 2020). Therefore, it can help explain how information entering such networks can eventually bias an entire population (Lorenz et al, 2011; Moussaïd et al, 2015), or how the interaction dynamics within a population can lead to the emergence of more accurate decisions in some cases (Kao and Couzin, 2014; Mann, 2018; Marshall et al, 2019), but also of groupthink and opinion polarization in others (Hegselmann and Krause, 2002; Janis, 1982).…”
Section: From Condorcet To Swarm Intelligence: a Brief Historical Per...mentioning
confidence: 99%
“…Observations of animal behavior [14], [26], [29], as well as experiments in humans [5] have demonstrated that dynamic switching between social and individual learning improves performance of the collaborative decision making process. Shifting from group driven activity to individual work is conjectured to act like brainstorming sessions, allowing to identify a wider range of possible solutions, since agents are not influenced by each other at all times.…”
Section: Dynamic Learning Rulesmentioning
confidence: 99%